A comparative evaluation of two investigational meningococcal ABCWY vaccine formulations: Results of a phase 2 randomized, controlled trial. Issue 21 (15th May 2015) - Block, Stan L.; Szenborn, Leszek; Daly, Wendy; Jackowska, Teresa; D'Agostino, Diego; Han, Linda; Dull, Peter M.; Smolenov, Igor
Highlights: MenABCWY vaccines were immunogenic against serogroups ACWY and serogroup B test strains. MenABCWY vaccines were immunologically noninferior to MenACWY-CRM. Reactogenicity profiles of MenABCWY vaccines were similar to 4CMenB with no safety concerns identified. Abstract: Background: A meningococcal vaccine protective against all major disease-associated serogroups (A, B, C, W and Y) is an unmet public health need. In this phase 2 observer-blinded, randomized, controlled study, two investigational meningococcal ABCWY vaccine formulations were evaluated to assess their immunological noninferiority to a licensed quadrivalent meningococcal ACWY glycoconjugate vaccine (MenACWY-CRM) for serogroups ACWY and immunogenicity against serogroup B test strains, as well as for formulation selection based on a desirability index (DI). Each investigational MenABCWY formulation contained recombinant protein and outer membrane vesicle (OMV) components of a licensed serogroup B vaccine (4CMenB) combined with components of MenACWY-CRM. Methods: A total of 484 healthy 10–25 year-old participants were randomized to receive two doses, two months apart, of an investigational MenABCWY formulation that contained either a full or one-quarter dose of OMV, 4CMenB alone, or a Placebo followed by MenACWY-CRM. Immunogenicity against each of serogroups ACWY and four serogroup B test strains was assessed by serum bactericidal assay with human complement (hSBA). MenABCWY formulations were compared by a DI based on key immunogenicity and reactogenicity parameters. Results: Seroresponse rates for serogroups ACWY were significantly higher after two doses of either MenABCWY formulation than after one dose of MenACWY-CRM: respectively, A: 90–92% vs. 73%; C: 93–95% vs. 63%; W: 80–84% vs. 65%; and Y: 90–92% vs. 75%. Prespecified noninferiority criteria were met. Both MenABCWY formulations induced substantial immune responses against serogroup B test strains, although 4CMenB responses were higher. Overall DIs for both MenABCWY formulations were similar. Reactogenicity profiles of the MenABCWY formulations were similar to each other and to that of 4CMenB. No vaccine-related serious adverse events were reported. Conclusions: Both investigational MenABCWY formulations elicited robust immune responses against serogroups ACWY and serogroup B test strains, and had acceptable reactogenicity profiles, with no safety concerns identified.